Out-of-Hospital Transesophageal Echocardiogram for Cardiac Arrest Resuscitation: The Initial Case. (2nd January 2020) - Merlin, Mark A.; Joseph, Joslyn; Hohbein, Janae; Ariyaprakai, Navin; Tanis, James; Tagore, Ammundeep
Abstract: Objective: The use of transesophageal echocardiogram (TEE) during cardiac arrest in the emergency department (ED) is a newer concept. TEE provides dynamic evaluation of chest compressions and rhythm analysis. Hand placement using external landmarks can result in maximal compression over the aorta, rather than the ventricles of the heart. Methods: We present the initial case of TEE performed in the out of hospital setting in an ambulance to facilitate cardiac arrest resuscitation using a disposable TEE probe. Results: This case is a proof of concept that TEE can be successfully performed and contribute to clinical care of cardiac arrest in the out of hospital setting. Conclusion: Further research needs to be performed to determine the clinical benefit, indications, and curriculum for emergency providers to successfully deliver this potentially valuable resource prior to widespread adoption.